TEACHING IN HIGHER EDUCATION: : TEACHER TRAINING AND THE CHALLENGE OF NEW INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) - Aparecida Estavas, Liliane; Elizia Sauer Andrade, Heidy (Revista Gênero e Interdisciplinaridade, 2021)
In the face of the advance of new technologies that has been occurring and reaching all sectors of society, this article presents a discussion guided by scholars about the changes that are occurring in education. It is important to think of how you can use so many resources available today while providing power changes in the teaching-learning process which until then was seen as something static and conservative. The task of the teacher in the twenty-first century is no longer ready to take the knowledge to the student, but rather has the role of acting as a mediator and facilitator in the process of knowledge construction. The changes that are taking place have led educators to seek knowledge and expertise so that they can perform satisfactorily their role in society.